Global change shifts trade‐offs among ecosystem functions in woodlands restored for multifunctionality. Issue 8 (22nd June 2021) - Fiedler, Sebastian; Monteiro, José A. F.; Hulvey, Kristin B.; Standish, Rachel J.; Perring, Michael P.; Tietjen, Britta
Abstract: Ecological restoration increasingly aims at improving ecosystem multifunctionality and making landscapes resilient to future threats, especially in biodiversity hotspots such as Mediterranean‐type ecosystems. Plants and their traits play a major role in the functioning of an ecosystem. Therefore, successful restoration towards long‐term multifunctionality requires a fundamental mechanistic understanding of this link under changing climate. An integrated approach of empirical research and simulation modelling with a focus on plant traits can allow this understanding. Based on empirical data from a large‐scale restoration project in a Mediterranean‐type ecosystem in Western Australia, we developed and validated the spatially explicit simulation model Modelling Ecosystem Functions and Services based on Traits (ModEST), which calculates coupled dynamics of nutrients, water and individual plants characterised by functional traits. We then simulated all possible combinations of eight plant species with different levels of diversity to assess the role of plant diversity and traits on multifunctionality, the provision of six ecosystem functions that can be linked to ecosystem services, as well as trade‐offs and synergies among the functions under current and future climatic conditions. Our results show that multifunctionality cannot fully be achieved because of trade‐offs among functions that are attributable to sets of traits that affect functions differently. Our measure of multifunctionality was increased by higher levels of planted species richness under current, but not future climatic conditions. In contrast, single functions were differently impacted by increased plant diversity and thus the choice and weighting of these functions affected multifunctionality. In addition, we found that trade‐offs and synergies among functions shifted with climate change due to different direct and indirect (mediated via community trait changes) effects of climate change on functions. Synthesis and application . With our simulation model Modelling Ecosystem Functions and Services based on Traits (ModEST), we show that restoration towards multifunctionality might be challenging not only under current conditions but also in the long‐term. However, once ModEST is parameterised and validated for a specific restoration site, managers can assess which target goals can be achieved given the set of available plant species and site‐specific conditions. It can also highlight which species combinations can best achieve long‐term improved multifunctionality due to their trait diversity. Abstract : With our simulation model Modelling Ecosystem Functions and Services based on Traits (ModEST), we show that restoration towards multifunctionality might be challenging not only under current conditions but also in the long‐term. However, once ModEST is parameterised and validated for a specific restoration site, managers can assess which target goals can be achieved given the set of available plant species and site‐specific conditions. It can also highlight which species combinations can best achieve long‐term improved multifunctionality due to their trait diversity.